Navigated multiplanar osteotomies for spinal primary bone tumors - Landriel Ibañez, Federico Alfonso (2022)
Establishing the proper diagnosis and rendering appropriate treatment of spinal primary bone tumors (SPBT) can result in definitive cures. Notably, malignant, or benign SPBT (i.e., with aggressive local behavior) generally require en bloc resection. Osteotomies of the vertebral body in more than 1 plane may avoid critical structures, preserve nerve functions, and reduce the volume of healthy bone resected. Here, our objective was to report how we planned and performed navigated multiplanar osteotomies for en bloc resection of 14 SPBT.